School based inclusive mentoring within the scope of an experiential l earning model (IEM) for teacher education - Yazici, Mahmut Serkan; Uzuner, Fatma Gül (Teaching and Teacher Education, 2024)
This research employed school-based Inclusive Experimental Monitoring (IEM) mentoring within the scope of Kolb's (1984) experiential learnin g model. This was used to support pre-service teachers, combined with their existing undergraduate education at a Turkish university. The st udy undertook a mixed research approach, using the pre- and post-test experimental group (n=11) and control group (n=11). Various quantitati ve and qualitative data collection tools were used, including a person al information form, scales, questionnaires, video recordings, and uns tructured observation. The results indicate that IEM has several posit ive outcomes for self-efficacy in inclusive education and readiness fo r the teaching profession. However, the study did not find any substan tial changes in attitudes towards individuals with special educational needs, despite some observed positive impacts. It is believed that in tegrating IEM into the entire undergraduate education process can lead to further development in this regard.
Keywords: Experiential learning; Inclusive education; Inclusive mentoring; Special needs; Teacher education